1994
DOI: 10.1080/14640749408401132
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and Explicit Forgetting: When is Gist Remembered?

Abstract: Recognition (YES/NO) and stem completion (cued: complete with a word from the list; and uncued: complete with the first word that comes to mind) were tested following either semantic or non-semantic processing of a categorized input list. Item/instance information was tested by contrasting target items from the input list with new items that were categorically related to them; gist/categorical information was tested by comparing target items semantically related to the input items with unrelated new items. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…Also in line with such theories, previous studies have shown that amnesic patients often show above-chance recognition, despite very poor recall (e.g., Hirst et al, 1986;Hirst & Volpe, 1982;Huppert & Piercy, 1977; but see Haist et al, 1992).2 A study using event-related potential methodology, moreover, provided evidence that the familiarity component of recognition is intact in amnesic patients, despite little evidence of retrieval (Smith & Halgren, 1989). Support for a dualprocess model is also available from numerous studies of normal subjects (e.g., Dorfman & Mandler, 1994;Jacoby & Dallas, 198! ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Also in line with such theories, previous studies have shown that amnesic patients often show above-chance recognition, despite very poor recall (e.g., Hirst et al, 1986;Hirst & Volpe, 1982;Huppert & Piercy, 1977; but see Haist et al, 1992).2 A study using event-related potential methodology, moreover, provided evidence that the familiarity component of recognition is intact in amnesic patients, despite little evidence of retrieval (Smith & Halgren, 1989). Support for a dualprocess model is also available from numerous studies of normal subjects (e.g., Dorfman & Mandler, 1994;Jacoby & Dallas, 198! ).…”
Section: Discussionmentioning
confidence: 87%
“…There is also neurophysiological evidence suggesting that amnesics show recognition based on familiarity, but not conscious retrieval (Smith & Halgren, 1989). In normal subjects, variables such as repetition and retention interval have been shown to affect priming (word-stem completion and perceptual identification) and recognition in a similar fashion (e.g., Dorfman & Mandler, 1994;Jacoby & Dallas, 1981).…”
mentioning
confidence: 99%
“…Following previous studies (e.g., Begg & Wickelgren, 1974;Dorfman & Mandler, 1994;Kintsch, Welsch, Schmalhofer, & Zimny, 1990;Reyna & Kiernan, 1994;see Brainerd & Reyna, 1993), it is assumed that the memory representation of the gist of the target information remains more accessible than the verbatim representation of these items. More specifically, the BL representations of the target items tend to be more accessible than their representations at the subordinate level, particularly over time (Pansky & Koriat, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, Huttenlocher and her colleagues (Huttenlocher, Hedges, & Duncan, 1988;Huttenlocher, Hedges, & Vevea, 2000; see also Bartlett, 1932;Brewer & Nakamura, 1984) proposed a model of episodic memory according to which two kinds of information are encoded when presented with a stimulus: Wne-grained information inherent to the stimulus and categorical information self-generated by the perceiver. The poorer the encoding or storage of the Wne-grained information, the more likely people are to combine this information with category information at recollection (categorical information will suVer of a slower rate of forgetting than item information; see Dorfman & Mandler, 1994). This process was coined "weighting with a prototype" by Huttenlocher and colleagues.…”
Section: Accentuation Evects In Face Memorymentioning
confidence: 96%